(untitled) (Research, Society and Development, 2022)
Diabetes mellitus (DM) is part of the group of chronic and multifactorial diseases, therefore, exogenous and endogenous factors are responsible for the development of this pathology. DM is considered a public health problem due to the high number of people affected by this pathology. DM1 is characterized by the autoimmune process that causes the destruction of pancreatic β cells, which produce insulin, by T lymphocytes. The genetic factor is a component that favors the development of the autoimmunity present in this disease. In the meantime, the objective of this article is to describe several factors associated with the development of DM1 with emphasis on the genetic condition, reporting the main polymorphisms associated with the appearance of this pathology. It is a theoretical referential developed through the search of publications obtained in the databases: PubMed, SciELO and NCBI. The descriptors diabetes mellitus, polymorphisms, DM1 and CTLA4 gene were used. Through the analysis of the survey of all material, it was possible to demonstrate that in addition to environmental factors, the genetic factor is also associated with the development of DM1 and several studies indicate CTLA4 polymorphisms to this pathology. It is concluded that it is necessary to carry out further studies on the CTLA4 gene, as well as highlights the need for DM carriers to exercise measures that increase the quality of life in order to prevent the occurrence of serious complications.